Turbo Throwing Game Application To Improve One-Hand Pass Skills In Basketball Learning At Arcamanik 04 Elementary School - Prawira, Alfian Satria; Lengkana, Anggi Setia; Rukmana, Anin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to improve the basic movement skills in basketball among students at SDN Arcamanik 04, which were not yet optimal. This study aims to improve the basic one-hand pass technique using the Turbo Throwing game for fifth-grade students at SDN Arcamanik 04. The study was conducted at SDN Arcamanik 04 on Physical Education for fifth-grade students in the 2024/2025 academic year, involving 24 students—13 boys and 11 girls. Classroom Action Research is the method used. The research design uses the Kemmis and MC. Taggart models, which focus on continuous reflection and action cycles. This research was carried out in three cycles, each consisting of planning, action implementation, monitoring and evaluation, as well as analysis and reflection. Student and teacher activity observation sheets were used to collect data during the monitoring and evaluation stage. The data was then analyzed using both quantitative and qualitative methods. In the first cycle, only one person completed it, resulting in a 4% pass rate. In the second cycle, 18 people passed, reaching a 75% pass rate. By the third cycle, all 24 participants completed it, achieving a 100% pass rate. This indicates that teacher-student activities in the first, second, and third cycles successfully met the learning process requirements. Based on the data above, the use of Turbo Throwing games can enhance the fundamental movement skills of one-handed passes.